Vacuolization in embryos on days 3 and 4 of in vitro development: Association with stimulation protocols, embryo development, chromosomal status, pregnancy and neonatal outcomes - Chen, Longbin; Zhang, Shuoping; Gu, Yifan; Peng, Yangqin; Huang, Zenghui; Gong, Fei; Lin, Ge (Frontiers in Endocrinology, 2022)
STUDY QUESTION: Is there a link between vacuolization in embryos on Days 3 and 4 and ovarian stimulation, gamete quality, embryonic development, euploidy, and clinical and neonatal outcomes? STUDY DESIGN, SIZE, DURATION: A retrospective cohort study that comprised 5703 embryos from 611 patients who underwent preimplantation genetic testing (PGT) and time-lapse monitoring of their embryos from August 2017 to September 2021. The vacuole-positive cycles produced at least one embryo that showed vacuolization on Day 3 and Day 4 while the vacuole- negative cycles did not. MAIN RESULTS: Vacuogenesis is weakly associated with the LH level on the day of the hCG trigger and with the numbers of retrieved oocytes. Compared to vacuole-negative embryos, the rates of blastocyst formation and good-blastocyst formation of embryos showing vacuole-positivity was significantly lower. We, however, observed no significant difference in the rates for euploidy, implantation, ongoing pregnancy, and live births between vacuole-positive and vacuole-negative embryos. The embryos in which vacuolated blastomeres were involved in embryonic compaction exhibited a significantly higher mosaicism rate but showed reduced implantation and ongoing pregnancy rates when compared with those not involved in embryonic compaction. Conclusion: The vacuolated embryo reflects a certain clinical value. This is the first-ever report in which the subsequent developmental fate of vacuole-containing cells was followed, and we ascertained that the vacuole-containing cells that did not participate in compaction experienced a lower mosaicism rate than embryos that participated in compaction. These results further support the hypothesis that embryos reject abnormal cells involved in compaction, and that vacuoles can be used as an abnormal morphological phenomenon to assist in the analysis of the mechanism(s) underlying embryonic self-correction.